CLCN1 Molecular Characterization in 19 South-Italian Patients With Dominant and Recessive Type of Myotonia Congenita - Orsini, Chiara; Petillo, Roberta; D'Ambrosio, Paola; Ergoli, Manuela; Picillo, Esther; Scutifero, Marianna; Passamano, Luigia; De Luca, Alessandro; Politano, Luisa (Frontiers in Neurology, 2020)
Myotonia congenita is a genetic disease characterized by impaired muscle relaxation after forceful contraction (myotonia). It is caused by mutations in the chloride channel voltage-sensitive 1 CLCN1 gene, encoding the voltage-gated chloride channel of skeletal muscle, ClC-1. According to the pattern of inheritance, two distinct clinical forms have been described, Thomsen disease, inherited as an autosomal dominant trait and Becker disease inherited as an autosomal recessive trait. We report genetic and clinical data concerning 19 patients – 12 familial and 7 sporadic cases – all but one originating from the Campania Region, in southern Italy. Twelve patients (63,2%) present Becker type myotonia and 7 (36,8%) Thomsen type. Sex ratio M:F in Becker type is 6:6, while in Thomsen myotonia 4:3. The age of onset of the disease ranged from 2 to 15 years in Becker patients, and from 4 to 20 years in Thomsen. Overall 13 mutations were identified, 10 located in the coding part of the gene (exons 1,3,4,5,7,8,13,15,21,22) and 3 in the intron part (introns 1,2,11). All the exon mutations but two were missense mutations. Some of them, such as c.2551 G>A, c.817G>A and c.86A>C recurred more frequently, other were private. About 70% of mutations was inherited with an autosomal recessive pattern, two (c.86A and c.817G>A) with both mechanisms. Two novel mutations were identified, never described in the literature: c. 826G>A;p.Gly276Ser and c.1403T>C; p.Phe486Ser, both associated with Becker phenotype. Two cases of contemporary CLCN1 three mutations, two of them inherited in cis on the same allele, were interestingly identified in two families, causing a different phenotype in the affected individuals. We confirm the occurrence of inter-individual and intra-familial phenotypic variability and, in Thomsen disease, an incomplete penetrance.